How do tougher immigration measures impact unauthorized immigrants? - Catalina Amuedo Dorantes; Thitima Puttitanun; Ana Martinez-Donate (Institute for the Study of Labor (IZA), 2013)
The recent impetus of tougher immigration-related measures passed at the state-level raises concerns about the impact of such measures on the migration experience, trajectory and future plans of unauthorized immigrants. In a recent and unique survey of Mexican unauthorized immigrants interviewed upon their voluntary return or deportation to Mexico, almost a third reports experiencing difficulties in obtaining social or government services, finding legal assistance or obtaining health care services. Additionally, half of them report fearing deportation despite all of them being unauthorized. When we assess how the enactment of punitive measures against unauthorized immigrants, such as E-Verify mandates, has impacted their migration experience, we find no evidence of a statistically significant association between these measures and the difficulties reported by unauthorized immigrants in accessing a variety of services. However, the enactment of these mandates infuses deportation fear and reduces inter-state mobility among voluntary returnees during their last migration spell, and helps curb deportees' intent to return to the United States in the near future.
Keywords: F22; O15; 330; immigration; policy; undocumented; illegal; unauthorized; Mexico; Migrationspolitik; Einwanderungsrecht; Illegale Einwanderung; Mexikaner; USA